Promoting Sustainable Environment Literacy Using the Power of Multimodality in E-Textbooks - The, Hery Yanto (Ma Chung Press, 2024)
This study explores the use of multimodal features in e-textbooks for English as a Foreign Language (EFL) in Indonesian high schools. For easier reference, the e-books are called EC-LE and LT-CF. Both were selected as they address topics that help with both learning a language and acquiring knowledge about the environment. The results revealed that the use of visuals, such as images, graphs, illustrations, and QR codes, in e-textbooks significantly facilitated students' comprehension. These features also increase the viability of abstract learning concepts relating to environmental issues. Both e-textbooks employ diverse modalities to cater to various learning styles. To visually represent environmental situations, EC-LE uses dynamic images and colorful layouts. These characteristics are particularly attractive to individuals who learn best through visual means. However, LT-CF effectively conveyed the environmental issue using informative visuals and detailed explanations, making it well-suited for students who prefer structured learning methods. Integrating multimodal components into these electronic textbooks aligns with educational concepts like constructivism and social semiotics. These principles emphasize the significance of visual and interactive tools in facilitating learning. QR codes in LT-CF enhance student engagement and digital literacy by connecting to multimedia resources that offer dynamic explanations and real-life illustrations, effectively complementing written information. These multimodal components enhance language proficiency, increase environmental awareness in EFL instruction, foster critical thinking in students, and offer a wide choice of instructional materials. Using this study's findings, educators can gain valuable insights and apply ways to use multimodalities in e-textbooks to improve the quality of their teaching.